Segmentasi Layanan Internet Banking - Sihotang, Ellen Theresia (Jurnal Manajemen dan Kewirausahaan, 2016)
The purpose of this study is to analyze internet banking’s users based on their experiences. It can be used to set marketing program of internet banking that appropriate with customers needs, in order to anticipate tight competition. This research methods starts with focus group discussion and clustering analysis to classify 312 respondents of internet banking users based on demographic, benefit and behavioral segmentation. The sampling method uses purposive sampling and snowball sampling. K-Means Clustering method’s produces four optimal clusters. The benefit orientation of the first cluster in on time saving. Second cluster, concern on the ease of getting and operating internet banking so this cluster does not need auxiliary features such as video guide to use internet banking. The third cluster’s orientation is on the modern lifestyle and the ease of getting and operating internet banking service with detailed daily mutation transaction The fourth cluster, concerns on the detailed daily mutation transaction but they are not sure with the security of personal data via internet banking. https://doi.org/10.26905/jmdk.v4i2.644